Analisis Faktor-faktor yang Mempengaruhi Repurchase Intention pada Minuman Boba di Kalangan Generasi Z Kota Batam - Nurjanah, Listia; Adeline, Adeline (Universitas Islam Kadiri, 2023)
This study aims to explore the factors that influence repurchase intention of boba drinks among generation Z in Batam City. By carrying out this research, it helps boba business entrepreneurs to understand which factor influences consumers to keep repurchase the boba drinks. The number of samples is 453 respondents with using purposive sampling method. The collected research data will be analyzed using Partial Least Squares with Structural Equation Modeling techniques. Based on the results of the analysis applied, it is proven that product quality, service quality, brand image, store atmosphere, and price have a significant positive effect on customer satisfaction and consumer satisfaction has a significant positive effect on repurchase intention.